The Role of Brand Image in Mediating The Influence of Electronic Word of Mouth (E-Wom) on Purchase Intention - Fazrin, Fauzi Ikhsan; Komariah, Kokom; Jhoansyah, Dicky (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study was conducted to examine the effect of Electronic Word of Mouth (E-WOM) on brand image and purchase intention, as well as the mediating role of brand image in the relationship between E-WOM and purchase intention. The phenomenon observed is the increasing role of online reviews and digital recommendations in shaping consumers' perceptions of brands and their purchasing decisions. This study used descriptive and associative methods with a quantitative approach. The study population was 356,410 residents of Sukabumi City, with a sample of 200 people randomly selected through probability sampling technique. Validity and reliability testing was conducted using SPSS version 23. The results showed that E-WOM had a significant effect on brand image with all items on the E-WOM variable and brand image declared valid (r_hitung > r_kritis). In addition, brand image also has a significant influence on consumer purchase intention. Brand image acts as a mediator that strengthens the influence of E-WOM on purchase intention. Cronbach's Alpha values for brand image, E-WOM, and purchase intention show high reliability (>0.60). In conclusion, E-WOM and brand image have an important role in shaping consumer purchase intention, with brand image strengthening the relationship between E-WOM and purchase intention. Effective marketing strategies should focus on improving brand image and leveraging E-WOM to drive consumer purchase decisions.